The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/masy.200850206
|View full text |Cite
|
Sign up to set email alerts
|

Treatment in Swelling Solutions Modifying Cellulose Fiber Reactivity – Part 2: Accessibility and Reactivity

Abstract: The reorganization of cellulose fibers by swelling treatments in alkali solutions results in numerous changes to fiber structure, causing changes of chemical reactivity in the fiber‐solution heterogeneous system. An important part of the change in chemical reactivity is the change of fiber accessibility because it results in exclusion of chemicals such as reagents or catalysts from the fiber. In the second of a two‐part series of papers, we examine the influence of changes in fiber accessibility and/or reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…5 Optical crosssections of lyocell filaments in a yarn dyed with 2% omf Cibacron Brilliant Red 4G-E following pretreatment with: a 0.0 mol dm -3 NaOH; b 1.5 mol dm -3 NaOH, c 2.0 mol dm -3 NaOH, d 5.0 mol dm -3 NaOH, and e 7.0 mol dm -3 NaOH. Scale bar is 20 lm Cellulose (2009) 16:481-489 485 this finding is in agreement with the findings of Bui et al (2008), where they reported an increase in porosity and accessibility in lyocell fibres after treatment with NaOH solution. The increase in %E, %F, and K/S from concentrations of 0.0-2.0 is attributed to a decrease in density and crystallinity of lyocell fibre with increasing concentration of NaOH in the pre-treatment bath (Goswami et al 2009); as adsorption and diffusion of dyes only occurs in the amorphous regions of a fibre this decrease in crystallinity affords the corresponding increase in dye sorption.…”
Section: Resultssupporting
confidence: 94%
“…5 Optical crosssections of lyocell filaments in a yarn dyed with 2% omf Cibacron Brilliant Red 4G-E following pretreatment with: a 0.0 mol dm -3 NaOH; b 1.5 mol dm -3 NaOH, c 2.0 mol dm -3 NaOH, d 5.0 mol dm -3 NaOH, and e 7.0 mol dm -3 NaOH. Scale bar is 20 lm Cellulose (2009) 16:481-489 485 this finding is in agreement with the findings of Bui et al (2008), where they reported an increase in porosity and accessibility in lyocell fibres after treatment with NaOH solution. The increase in %E, %F, and K/S from concentrations of 0.0-2.0 is attributed to a decrease in density and crystallinity of lyocell fibre with increasing concentration of NaOH in the pre-treatment bath (Goswami et al 2009); as adsorption and diffusion of dyes only occurs in the amorphous regions of a fibre this decrease in crystallinity affords the corresponding increase in dye sorption.…”
Section: Resultssupporting
confidence: 94%
“…A lower than the optimum NaOH concentration will lead to a decreased fiber swelling, thus reducing the pore size/porosity, which negatively affects the hemicelluloses diffusion through the fiber wall, thus, the overall hemicelluloses removal. Bui et al (2008) investigated the effect of alkaline treatment on the reactivity of regenerated cellulosic fibers, and the results indicated that the alkaline treatment can increase the porosity of the fiber wall and accessibility of fibers to NaOH.…”
Section: Proposed Concept Of Combined Mechanical Refining and Cce Formentioning
confidence: 99%
“…1,2 However, the strong swelling propensity of lyocell fibers in alkali solutions 3 changes substrate properties and may lead to alterations in the accessibility and reactivity of lyocell for chemicals and reagents and influence its performance in subsequent treatments. 4,5 In earlier work, 6,7 we examined the influence of alkali pretreatments on the performance of lyocell fabrics in subsequent resin finishing treatments. Fabric samples were pretreated with sodium hydroxide (NaOH; 120 g/L) or KOH (250 g/L) and resinfinished with a dimethyloldihydroxyethylene urea (DMDHEU) based product.…”
Section: Introductionmentioning
confidence: 99%